KONSEPTUAL PENDIDIK MENURUT PERSPEKTIF AL QURAN - Arif Nugraha; Karman; Cecep Anwar (Institut Nahdlatul Ulama Tasikmalaya, 2022)
Education in Islam is a complete guideline not only connotes authoritative teachings as educators, but also with guidance that is in accordance with Islamic teachings, students have ample space for movement in actualizing their potential. Educators are a very important component in the education system, for educators as a bridge for student achievement of predetermined goals, along with other related components. Educators have a noble position. The research method used uses a literature study with a qualitative approach to look for literacies related to educators from experts. Educators are expected to become uswatun hasanah who can set an example for their students as well as mentors and motivate students to welcome a better future